2017
DOI: 10.17556/erziefd.334989
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Tekrarı Yapan Öğrencilerin Akademik Erteleme Nedenleri

Abstract: The purpose of the research is to test the academic procrastination behaviours of 1st and 2nd grade high school students within the scope of a model with variables of self-recovery, life satisfaction, academic identification and motivation. The research that used the causal comparative method were carried out on 234 high school students who made a class repetition in the academic year of 2013-2014. 92 (40%) of the students in the research group were male and 140 (60%) of them were female students. As the tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
4
0
4
Order By: Relevance
“…Benzer şekilde sınıf tekrarı yapan öğrenciler üzerine yapılan başka bir çalışmada, akademik ertelemeyi en çok yordayan değişkenlerin motivasyon kaynakları olduğu görülmüştür (Kandemir, Palancı, İlhan ve Avcı, 2017).…”
Section: Bölüm I Gi̇ri̇şunclassified
“…Benzer şekilde sınıf tekrarı yapan öğrenciler üzerine yapılan başka bir çalışmada, akademik ertelemeyi en çok yordayan değişkenlerin motivasyon kaynakları olduğu görülmüştür (Kandemir, Palancı, İlhan ve Avcı, 2017).…”
Section: Bölüm I Gi̇ri̇şunclassified
“…As for the perception of academic self-efficacy, it is the feeling that one is capable of completing academic tasks with success (Yılmaz, Gürçay & Ekici, 2007). A large number of studies have demonstrated the importance of high academic self-efficacy for students (Yılmaz, Gürçay, and Ekici, 2007;Ekici, 2008;Kandemir, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the mediating role of procrastination in the effect of decision avoidance behavior on stress was also examined in this study. Studies show that procrastination behavior or procrastination is a widespread problem in individuals from all levels of society (Çakıcı, 2003;Kandemir et al, 2017;Cömert & Dönmez, 2018). The behavioral dimension of procrastination can be defined as the individual not doing what needs to be done on time or not making the necessary decisions on time (Senecal et al, 1997;cited by Aydoğan, 2008) and taking longer than necessary" (Senecal et al, 1997;cited in Çakıcı, 2003).…”
Section: Introductionmentioning
confidence: 99%